Transformative experience and informed consent to psychedelic-assisted psychotherapy - Jacobs, Edward (Frontiers in Psychology, 2023)
Just as psychedelic-assisted psychotherapy (PAP) represents a clinical innovation that may need to be accommodated with corresponding theoretical and methodological innovations, there is increasing awareness that the tools, normative frameworks, and standard practices of our clinical ethics may also need to be adapted, renewed, or replaced to accommodate its unusual features. Drawing on L. A. Paul’s work on ‘Transformative Experience’, I argue that the acute and long-term effects repeatedly reported following the administration of psychedelic drugs, including in clinical contexts, are epistemically inaccessible at the point of deciding to take them. By virtue of both the ‘peak’ or ‘mystical’ experiences that frequently arise during PAP, and the longer-term shifts to outlooks, values and priorities that follow, the processes of decision-making that are normatively expected of decisionally competent patients run aground. If this framing is correct, then prospective patients cannot meet the requirement of understanding that is one of the principal analytic components of informed consent as we standardly deploy it as a legitimising process for clinical intervention. The role of understanding in supporting two functions of informed consent —avoiding unauthorised trespass against patients and supporting values-aligned decision-making— is explored, and I argue that, while the normative standard for the first function may be met by extant suggestions for enhancing the consenting process for PAP, the latter function remains unattainable. In light of this, the consequences for ethical preparation of prospective patients are considered.